The Effect of Online Learning on Learning Interest and Digital Literacy of Students in terms of Gender (Gender-Based Comparative Causal Study of Students' Learning Interest and Digital Literacy in Distance Learning Due to the Covid-19 Primary School Pande - Rodiah, Siti; Sopandi, Wahyu (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
The implementation of online learning in elementary schools since the spread of the COVID- 19 viruses in Indonesia, so the background of this study is to determine the effect of learning interest in online learning on students' digital literacy in terms of individual competence based on gender. The method used is causal-comparative. The instrument in the form of a questionnaire regarding interest in learning and digital literacy in terms of individual competence based on gender. Data was collected using Google Forms. The study population was students at SDN Sukamukti 02, with a random sampling of 300 students, consisting of 175 girls and 125 boys. The research findings obtained are (1) there is a significant difference between the learning interest of male and female students with sig. 0.007; (2) there is no significant difference in the digital literacy skills of male and female students with sig. 0.091. So, the conclusion is that online learning that is carried out shows that there are differences in the learning interests of male and female students. However, the digital literacy skills of both male and female students during online learning did not show a significant difference. So, it can be said that the digital literacy skills of students are equal.